The development of the architectural object under the influence of social history - Bachinska, Ludmila (КНУБА, 2017)
Throughout the history of mankind people evolve: while they explore the space around themselves, they develop tools of work, language,the environment, gaining experience, developing skills, form of society, state, concept of beauty, methods of construction and more. Along with them architectural and urban objects change in function and layout, form and style, physical and spatial parameters, and the like. History of architecture and urban planning studies the main directions of urban art in different times, different era and as a cultural heritage of different peoples. However, until that time, it is not clear how the differences in socio-economic conditions and political structure in the States affect the formation of architectural and urban planning object. The study revealed that these factors are crucial. They affect the structure of society with a hierarchical construction of groups, where the representatives of the authorities, and the powers that protect them, are at the top. A certain structure of society requires certain methods of placement of the people in the city plan. Therefore, through the society as a method it is the implementation impact of these factors on the architectural object. The article considers structures of society in Soviet and world practice and the impact of social structure on the architectural features of dwellings in Ukraine in the XX – beginning of XXI centuries.
Keywords: man and his needs; economic relations; political conditions; society; architecture and urban planning.; 721.01